Perhitungan Ongkos Pemesinan Konvensional Menggunakan Macro Vba Excel pada Studi Kasus (Produk Roda Gigi Payung Ø65mm × Z24) - Junaidi, Abdul Khair; Hasan, Indra; Syofian Arief, Dosi; Duta H, Ryan (SURYA TEKNIKA, 2024)
In the conventional machining process, production costs are essential to know to determine the cost of making a product in any industrial manufacturing such as the SMK N 2 PEKANBARU machining workshop. Machining production costs are calculated based on machining time per product and machining operation costs. In calculating conventional machining costs, the VBA Excel macro is an application that can be used to calculate production costs. The Ø65mm × z24 umbrella gear product which is the research case study is a product that is machined by two conventional machining processes, namely lathe machining and milling machining. From the results of the research, the cost of conventional lathe machining, namely making gear wheels, is IDR 47,841/product, and the conventional milling process, namely making Z24 gears, is IDR 40,002/product, while the machining cost for lathe mastercam simulation is IDR 33,187/product and the machining cost for milling mastercam simulation is IDR 20,340/product. Machining costs are the product of operating costs per minute (cm) and machining time (tm). So, from the results of calculating machining and production costs, it is known that the product manufacturing costs or production costs for Ø65mm × Z24 umbrella gears are in the range of IDR 111,827 - IDR 146,143/product.